Candidaemia in a tertiary hospital in Nigeria - Rita O. Oladele (African Journal of Laboratory Medicine, 2014)
Background: Candidaemia is a widely-studied and reviewed topic in the developed world; however, there is a dearth of information on nosocomial candidaemia in Nigeria, despite the increasing use of more invasive therapeutic modalities, immunosuppressive agents and increasing incidence of immunosuppression as a result of malignancies and HIV. Objectives: To determine the hospital-based frequency of candidaemia in a tertiary hospital in Ibadan, Nigeria.